2013
DOI: 10.1088/1612-2011/10/3/035103
|View full text |Cite
|
Sign up to set email alerts
|

AQ-switched, mode-locked fiber laser using a graphene oxide-based polarization sensitive saturable absorber

Abstract: We demonstrate the use of a graphene oxide (GO)-deposited D-shaped fiber as a polarization sensitive saturable absorber for the implementation of a stable Q-switched, mode-locked fiber laser. Using both features of nonlinear saturable absorption and large polarization dependence loss of GO-deposited D-shaped fiber, stable Q-switched mode-locked pulses are readily obtained from an erbium-doped fiber ring laser through simple intra-cavity polarization control under a fixed pump power. It is shown that bursts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 22 publications
(32 reference statements)
1
61
0
Order By: Relevance
“…Figure 2D shows the autocorrelation trace of chirped (blue curve) and dechirped pulses (red curve). Lee et al reported a Q-switched mode-locked fiber laser by depositing GO to a D-shaped fiber [76]. Sobon et al compared the properties of GO with RGO as SAs in Er-doped mode-locked fiber laser, and showed that GO could be an efficient SA without reduction to RGO [82].…”
Section: Graphenementioning
confidence: 99%
“…Figure 2D shows the autocorrelation trace of chirped (blue curve) and dechirped pulses (red curve). Lee et al reported a Q-switched mode-locked fiber laser by depositing GO to a D-shaped fiber [76]. Sobon et al compared the properties of GO with RGO as SAs in Er-doped mode-locked fiber laser, and showed that GO could be an efficient SA without reduction to RGO [82].…”
Section: Graphenementioning
confidence: 99%
“…Researchers are still making considerable efforts to optimize the characteristics of graphene oxide to obtain more flexible pulse output. A number of research groups worldwide have used graphene oxide for passive Q-switching in fiber lasers [50][51][52][53][54][55][56][57][58]. In 2013, Yu et al demonstrated an ytterbium-doped Q-switched fiber laser for the first time [54].…”
Section: Graphene Oxide Based Q-switched Fiber Lasermentioning
confidence: 99%
“…Q-switched pulse lasers have been successfully developed basing on graphene (see Refs. [11][12][13][14]). …”
Section: Introductionmentioning
confidence: 99%